'Draw me after you': Toward an erotic theosis. Issue 2 (May 2023) - Davis, Aaron Brian
Abstract: In this article I propose an erotic theosis as a fruitful possibility for conceptualising our final participation in union with God in the beatific vision and for imaging said participation on earth. Particularly, I propose a synthesis of recent work from Oliver Crisp on theosis with that of Sarah Coakley on sexual desire as an especially helpful way in which to conceive of our ever-deepening participation in God's love. Further, this synthesis uses contributions from Erin Dufault-Hunter on the intersections of sexual desire and ethics as a catalyst for its recommendations.